1967
DOI: 10.1007/bf01213572
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography in diabetes mellitus a preliminary study

Abstract: Infrared thermography revealed characteristic abnormalities ia the emission patterns over the hands and feet of 16 young diabetics with or without manifest vascular complications. Infrared thermography seems to be a method well suited for fm'ther studies of circulation and metabolism in the hands and feet of diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

1968
1968
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…Previous works reported that hot spots occur mainly upon the metatarsal heads, great toe and heel, all of them areas of high foot pressure [8, 11]. Hot spots frequently lead in a high risk of ulceration thus their early detection is important.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works reported that hot spots occur mainly upon the metatarsal heads, great toe and heel, all of them areas of high foot pressure [8, 11]. Hot spots frequently lead in a high risk of ulceration thus their early detection is important.…”
Section: Methodsmentioning
confidence: 99%
“…According to several investigations, the presence of hot regions in the plantar area may indicate tissue damage, inflammation, and arteriovenous shunting, which could compromise the nutritive capillary flow and increase the predisposition to cutaneous ulceration [810]. For instance, Brånemark et al [11] found that diabetic patients present abnormal temperature patterns in feet and hands associated to common ulceration regions in a study made by using IR. Recently, Bharara et al [12] proposed an analysis based on the thermal profile of a foot wound in order to provide a healing wound index for diabetic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, IRT has been used to study young diabetes subjects with or without vascular complications. 11 The purpose of the present study was to examine the correlation between foot temperature and neuropathy in subjects with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…And keep the air flow stable, because air convection heating will directly affect the surface temperature [2] .…”
Section: Table 1 Distribution Of Age and Healthmentioning
confidence: 99%